ANALISIS MODEL PEMBELAJARAN PROJECT BASED LEARNING PADA MATA KULIAH PRAKTEK BATU BETON - Bazil Wiratomo (CV. ADIBA AISHA AMIRA, 2024)
This article discusses the Analysis of Project Based Learning (PjBL) in the course of Concrete Practice in Civil Engineering. Project Based Learning is one of the learning methods that can be applied to the Concrete Practice course, which is a practical course. Project Based Learning is a method of learning that utilizes projects/activities as a medium. This method demands students to explore and generate various learning outcomes. The purpose of this research is to address the lack of results obtained from the Concrete Practice course. The method used in this research is literature review, focusing on examining and analyzing several journals and articles related to the title that I have provided. Through comprehensive analysis of several relevant journals and articles, this article identifies the positive and negative impacts of PjBL on the Concrete Practice course, aiming to provide insights for educators and researchers in determining effective learning models.